2023
DOI: 10.3897/zookeys.1166.86986
|View full text |Cite
|
Sign up to set email alerts
|

An updated list of the Mexican herpetofauna: with a summary of historical and contemporary studies

Aurelio Ramírez-Bautista,
Lizzeth A. Torres-Hernández,
Raciel Cruz-Elizalde
et al.

Abstract: The growth in our knowledge of the diversity of the herpetofauna of Mexico has occurred over the period of approximately 445 years from the work of Francisco Hernández to that of a broad multinational array of present-day herpetologists. The work of this huge group of people has established Mexico as one of the most significant centers of herpetofaunal biodiversity in the world. This status is the result of a complex orography, in addition to diverse habitats and environments and the biogeographic history of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 62 publications
0
0
0
Order By: Relevance
“…Amphibians are the most threatened class of terrestrial vertebrates in terms of conservation [1,3], and according to Alroy [39], at the global level, the extinction of amphibians has accelerated since the 1980s and 1990s, with between 28 and 201 species going extinct and a current extinction probability for frogs of 66.1% [40]. Unfortunately, globally, Mesoamerica has the second highest probability of frogs going extinct, at 17.74%, with the main causes being deforestation, the introduction and expansion of the distribution of exotic species and the presence of the fungus Batrachochytrium dendrobatidis [3,39,40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Amphibians are the most threatened class of terrestrial vertebrates in terms of conservation [1,3], and according to Alroy [39], at the global level, the extinction of amphibians has accelerated since the 1980s and 1990s, with between 28 and 201 species going extinct and a current extinction probability for frogs of 66.1% [40]. Unfortunately, globally, Mesoamerica has the second highest probability of frogs going extinct, at 17.74%, with the main causes being deforestation, the introduction and expansion of the distribution of exotic species and the presence of the fungus Batrachochytrium dendrobatidis [3,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…In Mexico, the class Amphibia has a high global richness level, ranking fifth in the world in terms of diversity, with 430 species, of which 70% (300 species) are endemic to the country [1]. Mexico has the second most plethodontid species globally, with 132 species, of which 81% are endemic to the country [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These characteristics hold profound significance for Mexico and its fauna in terms of biodiversity, endemism, and conservation (Wilson et al, 2010). In this regard, Mexico ranks as one of the top countries worldwide, with approximately 1 421 species recorded in total (Flores-Villela & García-Vázquez, 2014;Parra-Olea et al, 2014;Ramírez-Bautista et al, 2023). This number has steadly increased due to new descriptions in both groups (e.g., López-Luna et al, 2018;Jiménez-Arcos et al, 2019;Arenas-Moreno et al, 2021;Ramirez-Bautista et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Herpetofaunal studies have identified Sinaloa as one of the ten most speciesdiverse states, with a total of 170 species, including 44 amphibians and 126 reptiles (Lemos-Espinal & Smith, 2020;Loc-Barragán et al, 2020;Castro-Bastidas & Serrano-Serrano, 2022;Lara-Resendiz & Jacobo-González, 2022;Aguirre-Zazueta et al, 2023b;Devitt et al, 2023;Grünwald et al, 2023;Payan-Cazares et al, 2023). These numbers represent approximately 12% of Mexico's herpetofauna, with 10.2% being amphibians and 12.9% reptiles according to Ramírez-Bautista et al (2023).…”
Section: Introductionmentioning
confidence: 99%